FAKTOR FAKTOR DOMINAN YANG BERHUBUNGAN DENGAN PENCEGAHAN PENYAKIT MALARIA DI KABUPATEN ASAHAN TAHUN 2023 - husna, zumrohtul; saragih, Erika; YessyAriescha, Putri Ayu (Jurnal Kajian Kesehatan Masyarakat, 2023)
Zumrohtul Husna.Dominant elements associated with Prevention of Malaria in Kisaran Barat District, Asahan Regency in 2023. Thesis, branch of grasp of Public health, school of Public fitness, Deli Husada Deli Tua health Institute. Asahan District is centered that allows you to dispose of malaria in 2025, but with a substantial growth inside the variety of fine instances remaining yr in 2 Districts and primarily based at the preliminary survey, particularly in West Kisaran and East Kisaran Subdistricts, there has been a trade in fame from the Low Endemic category to the mild Endemic class. the researchers are interested by inspecting the dominant factors associated with the prevention of malaria within the Asahan District, in particular inside the Kisaran Barat District.The studies method used in this take a look at became matched case-control. The populace in this take a look at were all high-quality malaria patients recorded inside the E-Sismal (electronic-Malaria Surveillance records device) and no longer malaria patients in the work place. Sidodadi sanatorium. The samples in this take a look at had been 39 instances and 39 controls. The statistics analysis used become univariate, bivariate the usage of the Chi-rectangular test, and multivariate evaluation the usage of the logistic regression check.The outcomes confirmed that there was a vast dating among using mosquito nets (p=0.020), the use of repellant (p=0.022), the set up of cord netting (p=zero.half), and the prevention of malaria. recommendations that can be given are to empower and mobilize the network to continue to be energetic in efforts to save you malaria, offer records to the network and additionally provide counseling associated with malaria on an ongoing basis, talk and endorse for the government to always actively help, and additionally provide motivation to the network for you to enhance malaria prevention measures.